2018
DOI: 10.1186/s12862-018-1224-z
|View full text |Cite|
|
Sign up to set email alerts
|

Enigmatic Diphyllatea eukaryotes: culturing and targeted PacBio RS amplicon sequencing reveals a higher order taxonomic diversity and global distribution

Abstract: BackgroundThe class Diphyllatea belongs to a group of enigmatic unicellular eukaryotes that play a key role in reconstructing the morphological innovation and diversification of early eukaryotic evolution. Despite its evolutionary significance, very little is known about the phylogeny and species diversity of Diphyllatea. Only three species have described morphology, being taxonomically divided by flagella number, two or four, and cell size. Currently, one 18S rRNA Diphyllatea sequence is available, with envir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…The use of both genes was proposed to more robustly derive the origin of environmental sequences, particularly in the case of fast‐evolving taxa, but this was based on Sanger sequencing of clone libraries (Marande, López‐García, & Moreira, ). Near full‐length 18S amplicons and even longer fragments including parts of the 28S gene have also recently been sequenced with PacBio for group‐specific investigations, demonstrating that long‐read high‐throughput sequencing is a promising complement to Illumina for investigating the environmental diversity of eukaryotes (Heeger et al, ; Orr et al, ). Here, we extended the approach to ~4,500 bp of the rDNA operon across the whole phylogenetic diversity of eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of both genes was proposed to more robustly derive the origin of environmental sequences, particularly in the case of fast‐evolving taxa, but this was based on Sanger sequencing of clone libraries (Marande, López‐García, & Moreira, ). Near full‐length 18S amplicons and even longer fragments including parts of the 28S gene have also recently been sequenced with PacBio for group‐specific investigations, demonstrating that long‐read high‐throughput sequencing is a promising complement to Illumina for investigating the environmental diversity of eukaryotes (Heeger et al, ; Orr et al, ). Here, we extended the approach to ~4,500 bp of the rDNA operon across the whole phylogenetic diversity of eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, PacBio sequencing has started to be applied to metabarcoding studies, primarily on prokaryotic 16S rDNA (Mosher et al, 2014;Schloss, Jenior, Koumpouras, Westcott, & Highlander, 2016;Wagner et al, 2016) and most recently on larger amplicons also including the 23S rDNA (Martijn et al, 2019). For eukaryotes, the 18S rDNA was nearly fully sequenced for targeted microbial groups (Orr et al, 2018), whilst longer regions also spanning the ITS and the large subunit (LSU) 28S gene were used to analyse fungal diversity (Heeger et al, 2018;Tedersoo & Anslan, 2019;Tedersoo, Tooming-Klunderud, & Anslan, 2018). These studies showed that in spite of the high error rates of PacBio, when applying a corrective process based on multiple sequence passes (Circular Consensus Sequences [CCS]) together with rigorous quality filtering, long-amplicon sequencing is emerging as a robust approach for studying environmental diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Using PacBio, near‐full‐length 18S rRNA gene sequences were obtained from environmental samples for the enigmatic protistan group of Diphyllatea (Orr et al. ). A few other studies mainly targeting fungal diversity were able to sequence longer fragments including also the ITS and 28S rRNA gene (Heeger et al.…”
Section: Current and Future Directionsmentioning
confidence: 99%
“…The use of both genes was proposed to more robustly derive the origin of environmental sequences, particularly in the case of fast-evolving taxa, but this was based on Sanger sequencing of clone libraries (Marande, López-García, & Moreira, 2009). Near full-length 18S amplicons and even longer fragments including parts of the 28S have also recently been sequenced with PacBio for group-specific investigations, demonstrating that long-read high-throughput sequencing is a promising alternative to Illumina for investigating the environmental diversity of eukaryotes (Heeger et al, 2018;Orr et al, 2018). Here, we extended the approach to ~4500bp of the rDNA operon across the whole phylogenetic diversity of eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…In the last two years, PacBio sequencing has started to be applied to metabarcoding studies, primarily on prokaryotic 16S rDNA (Mosher et al, 2014;Schloss, Jenior, Koumpouras, Westcott, & Highlander, 2016;Wagner et al, 2016) and most recently on larger amplicons also including the 23S rDNA (Martijn et al, 2017). For eukaryotes, the 18S rDNA was nearly fully sequenced for targeted microbial groups (Orr et al, 2018), whilst longer regions also spanning the ITS and the 28S gene were used to analyze fungal diversity (Heeger et al, 2018;Tedersoo, Tooming-Klunderud, & Anslan, 2018). These studies showed that in spite of the high error rates of PacBio, when applying a corrective process based on multiple sequence passes (Circular Consensus Sequences -CCS) together with rigorous quality filtering, long-amplicon sequencing is emerging as a robust approach for studying environmental diversity.…”
Section: Introductionmentioning
confidence: 99%